Grammatical Strategies of Persuasion in President Prabowo Subianto’s D-8 Summit 2024 Speech - Herawati, Nanik; Putut Setiyadi, Dwi Bambang; Hersulastuti, Hersulastuti; Haryono, Purwo; Widiyanti, Sukasih Ratna (JOLLT Journal of Languages and Language Teaching, 2025)
A leader’s speech in an international forum functions as a strategic rhetorical instrument to convey vision, foster solidarity, and assert diplomatic presence. This study analyzes the speech delivered by President Prabowo Subianto at the 2024 D-8 Summit, which centered on the call for unity among Muslim nations. Using a qualitative discourse analysis approach, the study applies Aristotelian rhetorical appeals: ethos, pathos, and logos, within a lexicogrammatical framework. The dataset comprised 37 clauses, examined through mood types, speech functions, and polarity. The findings reveal that declarative mood was dominant (62%), establishing ethos through the delivery of credible statements and objective facts. A Pathos was conveyed via both declarative and imperative moods, reflecting emotional intensity through critical remarks, expressions of solidarity, and direct appeals. Logos was constructed through the inclusion of statistical data and historical references, supporting argumentative coherence. The consistent use of inclusive pronouns such as "we" reinforced collective identity, while the interplay of positive and negative polarity created rhetorical tension that enhanced emotional engagement. This study demonstrates how grammatical choices underpin rhetorical strategies, offering insights into political communication. The findings have implications for diplomatic speechwriting and rhetorical pedagogy, especially in contexts emphasizing cross-national solidarity and advocacy.